IMPLEMENTATION OF SUBJECTS OF ECONOMY OF PROCESSING APPROACH IN TERMS OF TURBULENT ENVIRONMENT - Verbovska , L.S.; Hamuliak, N.M.; Gladun , O.V.; Muts , Yu. S. (The actual problems of regional economy development, 2019)
The article highlights the main components of applying a process approach to improving business processes by business entities. The conditions of flexibility in the context of environmental impact are substantiated. Offered tools and methods that are based on relationships within the entity itself are a fairly practical component aimed at a common goal of improving business process. The concept of Agile Management, derived from computer science and the Flexible Enterprise Model, is considered. Flexibility providers have been identified as the means by which the necessary skills to build appropriate practices, tools, and methods can be achieved and cannot act as a result of constraints on the internal and external environment, is the concept of internal organization policies and resource configuration. Process management is proposed, which should be based on a process-based five-resource method, which is to identify areas for adapting an entity to global change, development strategies, human potential, IT -systems. The tasks of the Agile Management concept and the Flexible Enterprise Model are distinguished and the expectation that having access to the necessary information, the chief / TOP-managers of the entity will be able to provide high added value in improving business processes. It is proved that implementation of the process approach to management is a major component of increasing the competitive advantages of economic entities in the face of global change.